2021
DOI: 10.1007/s10389-020-01432-7
|View full text |Cite|
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices related to the COVID-19 pandemic among Bangladeshi youth: a web-based cross-sectional analysis

Abstract: Aim This study aimed to assess knowledge, attitudes, and practices (KAP) toward COVID-19 among youth in Bangladesh. Subject and methods A cross-sectional survey was conducted from 5 May to 25 May 2020. People aged between 18 and 35 years were approached via social media to complete an online questionnaire that consisted of socio-demographic information and KAP toward COVID-19. Descriptive statistics, t-tests, one-way analysis of variance (ANOVA), and multiple logistic regression analyses were conducted. Result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
62
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 27 publications
33
62
4
2
Order By: Relevance
“…Knowledge regarding COVID-19 vaccinations was not significant in terms of participants’ sex. This finding is similar with other studies in Bangladesh demonstrating no significant sex differences in knowledge regarding COVID-19 [24,25]. This finding is similar to studies concerning knowledge towards COVID-19 (not vaccinations) conducted in Bangladesh which reported that males had marginally higher scores in knowledge regarding COVID-19 than females [26,27].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Knowledge regarding COVID-19 vaccinations was not significant in terms of participants’ sex. This finding is similar with other studies in Bangladesh demonstrating no significant sex differences in knowledge regarding COVID-19 [24,25]. This finding is similar to studies concerning knowledge towards COVID-19 (not vaccinations) conducted in Bangladesh which reported that males had marginally higher scores in knowledge regarding COVID-19 than females [26,27].…”
Section: Discussionsupporting
confidence: 90%
“…According to our study, participants with a higher level of education were found to have more knowledge about COVID-19 vaccinations, which is also supported by previous research. Similar scenarios were found in other earlier studies in Bangladesh, illustrating that individuals with a higher educational background showed more knowledge regarding COVID-19 [25,29]. It may be the case that more educated people are more knowledgeable and concerned about their health and well-being, through access to more information sources, and become more engaged in life events that could impact them [30], such as COVID-19 vaccinations.…”
Section: Discussionsupporting
confidence: 81%
“…These particular two vulnerable groups, in general, fall into the lowest wealth index category lacks awareness [44]. Farmers mostly reside in rural areas, and a recent study suggested that compared to urban, rural residents were particularly at risk of COVID-19 due to their significantly lower level of knowledge [45]. Additionally, they perceive the severity of the pandemic lightly [38].…”
Section: Discussionmentioning
confidence: 99%
“…from diverse occupations [3,9,[19][20][21]. The major strengths of the study are its large sample size and district-wise mapping, which provides a better insight of the scenario towards COVID-19 in Bangladesh.…”
Section: Plos Onementioning
confidence: 99%
“…This can reduce the government's burden in combating the outbreak strategies. There are a few studies [3,9,[19][20][21] that have been conducted in the country which address this issue. However, these studies are nonrepresentative with limited sample sizes and do not provide any (i) district-wise mapping regarding knowledge and preventive behaviors, or (ii) use any models.…”
Section: Introductionmentioning
confidence: 99%